2004
DOI: 10.21861/hgg.2004.66.01.02
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Spatial Structure of a City: the Example of Zagreb

Abstract: This work provides a summarized overview of select aspects, concepts and results of foreign and Croatian research into the socio-spatial structure of a city. The status of the sociospatial structure of Zagreb has been determined through an analysis of statistical indicators of the socio-economic status of its population. The results show similarities between the socio-spatial structure of Zagreb and other postsocialist cities. The spatial pattern from the pre-transition period has been retained, and it is refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Najniži stupanj je park u jednom stambenom naselju (susjedstvu, mikrorajonu), a najveći zelene površine u prigradskoj zoni." Hijerarhijski sistem zelenih površina s obzirom na funkcionalno-gravitacijski potencijal moguće je prepoznati i na primjeru Zagreba, a čine ga: a) parkovi u susjedstvu (Vresk, 1990), b) trgovi-parkovi (primjerice trgovi istočnog dijela Lenucijeve potkove -Trg Nikole Šubića Zrinskog, Strossmayerov trg, Tomislavov trg; Prelogović, 2000), c) gradski parkovi (npr. Maksimir, Ribnjak; Chiesura, 2004;Dolenc, 2010), d) rekreacijsko-sportske zone (primjerice Jarun, Bundek, savski nasip; Štulhofer, 1995) te e) zelene površine u prigradskoj zoni (Vresk, 1990), među kojima se značenjem ističu šumska područja s višestrukom funkcijom (Vresk, 2002), kao što je Dotršćina, te zaštićena područja (npr.…”
Section: Uvodunclassified
“…Najniži stupanj je park u jednom stambenom naselju (susjedstvu, mikrorajonu), a najveći zelene površine u prigradskoj zoni." Hijerarhijski sistem zelenih površina s obzirom na funkcionalno-gravitacijski potencijal moguće je prepoznati i na primjeru Zagreba, a čine ga: a) parkovi u susjedstvu (Vresk, 1990), b) trgovi-parkovi (primjerice trgovi istočnog dijela Lenucijeve potkove -Trg Nikole Šubića Zrinskog, Strossmayerov trg, Tomislavov trg; Prelogović, 2000), c) gradski parkovi (npr. Maksimir, Ribnjak; Chiesura, 2004;Dolenc, 2010), d) rekreacijsko-sportske zone (primjerice Jarun, Bundek, savski nasip; Štulhofer, 1995) te e) zelene površine u prigradskoj zoni (Vresk, 1990), među kojima se značenjem ističu šumska područja s višestrukom funkcijom (Vresk, 2002), kao što je Dotršćina, te zaštićena područja (npr.…”
Section: Uvodunclassified
“…In studies conducted in American, British and other western cities the opposite has been observed, since the process of socio-economic polarisation of urban space is much more evident and longer present there than in Croatian cities. In the post-socialist period, the process of socio-economic polarisation of urban space has started to develop more intensively (Prelogović, 2004;. As these results suggest, in Rijeka, this process is still not expressed enough for household income, educational attainment or property value to affect neighbourhood satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…A prerequisite to establishing new laws and regulation of relations between actors in the spatial planning was the new territorial organisation adopted in 1992 through the Act on Counties, Cities and Municipalities [Zakon o područjima županija, gradova i općina] (1992), which divided the Croatian territory into 21 counties including the City of Zagreb. The new legislative framework in the field of planning started in 1994 by passing the Act on Spatial Planning [Zakon o prostornom uređenju] (1994) with a number of amendments (Act on Spatial Planning, 1994;1998;2000;2002;2004). It defined the structure and hierarchy of spatial planning documents and a system of spatial planning for the entire Croatian territory, with a commitment to harmonise the spatial planning documents of lower territorial units with spatial planning documents of higher territorial units.…”
Section: Legislative and Spatial Planning Frameworkmentioning
confidence: 99%